Failure analysis of a coupled shaft from a shredder. (September 2019) - Vicente, Carlos M.S.; Sardinha, Manuel; Reis, Luís
Abstract: In this work the failure analysis of a coupled shaft from a shredder is presented. The failure analysis was performed using both experimental methods (visual and microscopic inspection, tensile and hardness tests) and theoretical calculations (stress analysis) aiming to determine the root causes of failure of the coupled shaft. The failure of the shaft occurred due to fatigue, on a perpendicular plane to the rotation axis, in the region of the coupling transverse hole. The shaft fracture surface presents characteristics of fatigue due to torsion combined with bending high loads, with an associated strong plastic deformation. The contribution of bending solicitations related with radial misalignment between the shaft and the shredder module was evaluated. The radial misalignment plays an important role on the failure of the shaft. For the reported life service of the shaft under maximum torsional moments, and considered working conditions, the design guidelines of radial misalignments compromise the structural integrity of the shaft in the shredder system. Recommendation regarding the design and assembly of the shaft are also presented. Highlights: The root causes of failure of the coupled shaft are determined. The shaft fractured surface was investigated by visual and microscopic examination. The fracture presents features of fatigue associated with high plastic deformation. The radial misalignment is quantified and plays an important role on the failure.